TYPES OF INFORMATION SYSTEMS: TYPES OF INFORMATION SYSTEMS - Ivanov, Sabin; Doychinova, Klaida (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The report shows ways to divide information systems into different types. Although the separation is artificial, it is important and is the basis for the formation of various GIS applications. Non-land GIS are focused on the population, housing policy, economic and political activity of the population.